Designing graphic illusions. (SendPoints Publishing Co., Ltd., 2019)
Optical illusions can be seen everywhere in our lives, from interior design, installation, 3D art, product, to brand identity, book cover, and typeface design. They can always draw a wide public attention and bring economic benefits. This book has summarized 14 principles of visual illusion and 8 creation techniques, and included more than 60 amazing optical illusion artworks. Most important, it enables readers to create visual illusion flexibly and effectively either for personal interest or for commercial project.